Expression of the heat-modifiable major outer membrane protein of Haemophilus influenzae type b is unrelated to virulence. - Hanson, M. S. (1989)
The heat-modifiable major outer membrane protein (P1) of Haemophilus influenzae type b (Hib) has been shown to be both exposed on the cell surface and capable of inducing the synthesis of antibodies protective against experimental Hib disease. Chemical mutagenesis of a recombinant plasmid containing the Hib gene encoding P1 resulted in inactivation of P1 expression by this plasmid. The mutated P1 gene was transformed into Hib to obtain an isogenic mutant lacking only the ability to synthesize this surface protein. In addition, the P1 gene was inserted into a plasmid shuttle vector and used to construct a recombinant Hib strain that overexpressed the P1 protein. Lack of P1 expression did not affect the ability of Hib to grow in vitro. Neither the absence nor the overproduction of P1 affected expression of capsular polysaccharide and lipooligosaccharide by Hib. The P1-negative mutant and the P1-overexpressing strain were both as susceptible to the bactericidal activity of pooled normal human serum as was the wild-type parent strain, while the P1-negative mutant was as resistant to the bactericidal activity of normal infant rat serum as was the wild-type parent strain. The P1-negative mutant was no less virulent than was the wild-type parent strain in an animal model system, such that both the numbers of animals infected by this mutant and the mean magnitudes of the resultant bacteremias were essentially identical to those obtained with challenge by the wild-type parent strain. Similarly, overexpression of P1 did not detectably affect the virulence of Hib. These data indicate that this protective protein antigen plays no detectable role in the expression of virulence by Hib, as assessed in an animal model system.